Structure perfection of large-size KDP crystals grown by various techniques - Puzikov, V.M.; Tkachenko, V.F.; Tsurikov, V.A. (Functional Materials, 2008)
The structure perfection of large-size KDP single crystals grown from nominally pure raw material by recirculation and solution temperature lowering techniques has been studied using the precision three-crystal X-ray diffractometry. The distribution inhomogeneity of the crystal lattice parameters Δd/d over the grown crystal volume has been established. The crystals grown by the solution recirculation technique have shown an improved structure perfection. Методами прецизійної трьохкристальної рентгенівської дифрактометрії досліджено досконалість структури великогабаритних монокристалів КОР, вирощених із номінально чистої сировини методами рециркуляції та зниження температури розчину. Встановлено неоднорідність розподілення параметрів кристалічної гратки Δd/d в об'ємі вирощених кристалів. Більш висока досконалість структури спостерігається для кристалів, вирощених методом рециркуляції розчину. Методами прецизионной трехкристальной рентгеновской дифрактометрии исследовано совершенство структуры крупногабаритных монокристаллов KDP, выращенных из номинально чистого сырья методами рециркуляции и снижения температуры раствора. Установлена неоднородность распределения параметров кристаллической решетки Δd/d в объеме выращенных кристаллов. Более высокое совершенство структуры наблюдается для кристаллов, выращенных методом рециркуляции раствора.